A Phenomenological Study of Felt Sense among Beginning Counselors - Perry Peace; Sondra Smith-Adcock (Teaching and Supervision in Counseling, 2020)
This qualitative study explored the lived experiences of felt sense among six graduate counseling students. Each participant engaged in two semi-structured interviews and completed a journal of felt sense experiences. A Hermeneutic phenomenological method was used to analyze interview transcripts and journals. Findings, as well as implications for counselor education, supervision, and counseling practice, are discussed.
Keywords: felt sense; counselor preparation; counselor development; phenomenology